2010
DOI: 10.1590/s0037-86822010000200017
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniose visceral: estudo retrospectivo de fatores associados à letalidade

Abstract: The results suggest that the prognosis becomes poor when associated with the presence of comorbidities, and that the treatment needs to be carefully administered to minimize mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
2
47

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 9 publications
6
35
2
47
Order By: Relevance
“…This result may be related to the incomplete development of the immune system in the children the comorbidity of HVL with chronic diseases, and the decline of the immune system in the elderly (33) (34) (35) (36) . The higher incidence in males is consistent with the literature (33) (34) (36) (37) . The mortality rate was also higher in males and those aged 60 and older, which may also be related to immune factors and complications from pre-existing conditions.…”
Section: Discussionsupporting
confidence: 93%
“…This result may be related to the incomplete development of the immune system in the children the comorbidity of HVL with chronic diseases, and the decline of the immune system in the elderly (33) (34) (35) (36) . The higher incidence in males is consistent with the literature (33) (34) (36) (37) . The mortality rate was also higher in males and those aged 60 and older, which may also be related to immune factors and complications from pre-existing conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have demonstrated multiple causes of death and have identifi ed clinical risk factors as important predictive markers 9,10,20,21 . The host immunological response to the parasite is certainly a major clinical determinant in VL 10,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Ao se percorrer os eixos rodoviários e ferroviários de São Paulo, observam-se padrões semelhantes de expansão urbana e mobilidade da população em outras cidades do interior paulista, como Araçatuba-SP, Presidente Prudente-SP e Dracena-SP. 16,17 O predomínio de casos masculinos, como descrito em outros trabalhos disponíveis na literatura, 18,19 sugere que homens estariam mais expostos ao vetor, provavelmente em função de desempenharem atividades ocupacionais e comportamentais mais próximas à fonte de infecção. 20 Considerando-se que cerca de 40% dos casos foram registrados em crianças com menos de 10 anos e que esse segmento etário corresponde a menos de 15% da população de Bauru-SP, fica evidente a alta carga de morbidade nessa faixa etária.…”
unclassified